Analisis Penetapan Harga Jual Beli Makanan pada Sistem Prasmanan Perspektif Prinsip Keadilan Ekonomi Islam - Anisa Fitri Al Husna; Imam Prawoto; Rizal Maulana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines pricing mechanisms in the buffet system at Wisma Tamu Al Ishlah Restaurant from the perspective of Islamic economic justice principles. This research is crucial given the limited studies that analyze buffet pricing practices from an Islamic economic perspective, particularly in a pesantren (Islamic boarding school) environment. This research adopts a qualitative approach with field research methods, utilizing interviews, observations, and documentation for data collection. The findings indicate that the pricing mechanism at Al Ishlah Restaurant employs a cost-based method, setting prices based on raw material costs, capital, operational expenses, and production services, adjusted according to the types of food selected by customers. Generally, the pricing practices at Wisma Tamu Al Ishlah Restaurant align with Islamic economic justice principles, ensuring that no party is disadvantaged and upholding honesty in transactions. Prices are established through mutual agreement between the restaurant and the customer, ensuring fairness. However, price transparency presents a challenge that could affect consumer perceptions. This research contributes to the development of Islamic economic theory in the culinary business context and provides recommendations to enhance justice in buffet pricing..